(untitled) (Journal of Parents and Teachers, 2015)
In varietate, Concordia, the European Union slogan reflects so accurate their values: bigger social cohesion (where all citizens in the European Union have the same educational opportunities, mobility and employability), bigger sense of belonging (whose people are culturally diverse but share the values of democracy and respect for pluralism) and central education not so much in content acquisition (only); but in competitions (which represent the practical application of these contents in a useful performance or useful way for real life). Education has taken the crucial role in this newEurope.